Towards a better cannabis drug - Mechoulam, Raphael (Blackwell Publishing Ltd, 2013)
This commentary discusses the importance of a new study entitled ‘Cannabidiol attenuates deficits of visuo-spatial associative memory induced by Δ(9)-tetrahydrocannabinol’ by Wright et al. from the Scripps Institute in La Jolla, California. The results in this study show that the non-psychoactive cannabis constituent cannabidiol opposes some, but not all, forms of behavioural and memory disruption caused by Δ(9)-tetrahydrocannabinol in male rhesus monkeys. LINKED ARTICLE: This article is a commentary on the research paper by Wright et al., pp 1365–1373 of this issue. To view this paper visit http://dx.doi.org/10.1111/bph.12199